2015
DOI: 10.24910/jsustain/3.1/3745
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon Haiyan 2013 Evacuation Preparations and Awareness

Abstract: Category 5 Typhoon Haiyan (known as Yolanda in the Philippines) made landfall in the Philippines on the 8 th November 2013 at almost the peak of its power, devastating the islands of Leyte and Samar, amongst other places. The present paper analyses the degree of awareness and preparedness of the islands of Samar and Leyte in the Philippines against storm surges prior to the arrival of typhoon Haiyan. The analysis was based on field surveys and interviewed with a variety of local residents and officials conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…This is because the calculated typhoon intensity is underestimated compared with the best track data, causing relatively weaker wind induced setup, in places like TaCH. Otherwise, the simulated time history of water level agrees well with eyewitness accounts by local residents, where the water first retreated away from the shoreline (to a level of -1 m, up to 100 m away in some places) and then quickly rose to a height of around 5 m (Esteban et al 2015). Shibayama et al (2014) indicated these rapid changes in water levels were associated with sudden changes in wind direction and can cause tsunami-like hydraulic bore in the large front of the storm surge, as observed by coastal residents.…”
Section: Boundary Conditions Under Global Warming Scenariossupporting
confidence: 54%
See 1 more Smart Citation
“…This is because the calculated typhoon intensity is underestimated compared with the best track data, causing relatively weaker wind induced setup, in places like TaCH. Otherwise, the simulated time history of water level agrees well with eyewitness accounts by local residents, where the water first retreated away from the shoreline (to a level of -1 m, up to 100 m away in some places) and then quickly rose to a height of around 5 m (Esteban et al 2015). Shibayama et al (2014) indicated these rapid changes in water levels were associated with sudden changes in wind direction and can cause tsunami-like hydraulic bore in the large front of the storm surge, as observed by coastal residents.…”
Section: Boundary Conditions Under Global Warming Scenariossupporting
confidence: 54%
“…In addition to measuring the storm surge heights, the team also interviewed local residents to understand evacuation patterns and the awareness of local residents about the dangers posed by the typhoon (Esteban et al , 2015. The area surveyed included the coastal zones of Samar and Leyte islands, which meet at the San Pedro and San Pablo Bay, Leyte Gulf.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when elaborating a storm surge hazard map, the effects of overtopping waves are seldom included. As shown by previous storm surge events [25][26][27], the extent of the damage to human being depends on the level of people's awareness and preparedness. Considering this, it is important to make coastal residents aware that inundation could occur even if they are outside of the predicted storm surge inundation area.…”
Section: Lessons For Japanese Disaster Risk Managementmentioning
confidence: 99%
“…Land subsidence in Asian megacities (Kaneko and Toyota, 2011;Takagi et al, 2016a). surge as many of them had only just heard the term for the first time. Many people expressed the view that it would have been better for authorities and media to describe it by a simpler vocabulary such as a tsunami Esteban et al, 2015Esteban et al, , 2016Mikami et al, 2016). In this regard, the term "flood" (Indonesian: "banjir") is unlikely to evoke the real danger that would be caused by a dyke-break event, since local inhabitants may imagine a gradually increasing persistent inundation as it always happens, particularly in Jakarta.…”
Section: Introductionmentioning
confidence: 99%